Low interannual precipitation has a greater negative effect than seedling herbivory on the population dynamics of a short‐lived shrub, Schiedea obovata. Issue 1 (26th November 2017) - Bialic‐Murphy, Lalasia; Gaoue, Orou G.
Abstract: Climate projections forecast more extreme interannual climate variability over time, with an increase in the severity and duration of extreme drought and rainfall events. Based on bioclimatic envelope models, it is projected that changing precipitation patterns will drastically alter the spatial distributions and density of plants and be a primary driver of biodiversity loss. However, many other underlying mechanisms can impact plant vital rates (i.e., survival, growth, and reproduction) and population dynamics. In this study, we developed a size‐dependent integral projection model (IPM) to evaluate how interannual precipitation and mollusk herbivory influence the dynamics of a Hawaii endemic short‐lived shrub, Schiedea obovata (Caryophyllaceae). Assessing how wet season precipitation effects population dynamics it critical, as it is the timeframe when most of the foliar growth occurs, plants flower and fruit, and seedlings establish. Temporal variation in wet season precipitation had a greater effect than mollusk herbivory on S . obovata population growth rate λ, and the impact of interannual precipitation on vital rates shifted across plant ontogeny. Furthermore, wet season precipitation influenced multiple vital rates in contrasting ways and the effect of precipitation on the survival of larger vegetative and reproductively mature individuals contributed the most to variation in the population growth rate. Among all combination of wet season precipitation and herbivory intensities, the only scenario that led to a growing population was when high wet precipitation was associated with low herbivory. Our study highlights the importance of evaluating how abiotic factors and plant–consumer interactions influence an organism across its life cycle to fully understand the underpinning mechanisms that structure its spatial and temporal distribution and abundance. Our results also illustrate that for short‐lived species, like S. obovata, seedling herbivory can have less of an effect on the dynamics of plant populations than decreased interannual precipitation. Abstract : Plant endangerment is driven by complex interactions of multiple environmental stressors, which can have varying effects on plant vital rates and ultimately population dynamics. In this study, we used a size‐dependent integral projection model (IPM) to evaluate how interannual precipitation and mollusk herbivory influenced the temporal variability in the dynamics of a Hawaii endemic short‐lived shrub, Schiedea obovata (Caryophyllaceae). Our results illustrate that for short‐lived species, like S. obovata, seedling herbivory can have less of an effect on the dynamics of plant populations than abiotic conditions.